2019
DOI: 10.1016/j.fishres.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparing size selectivity of traditional and knotless diamond-mesh codends in the Iceland redfish (Sebastes spp.) fishery

Abstract: The size selectivity and usability of two diamond mesh codends, a traditional two-panel codend versus an experimental four-panel ultra-cross knotless mesh codend, were compared using the covered codend method in the Iceland redfish (Sebastes norvegicus and S. viviparous) fishery. Results showed that there was no significant difference in size selectivity between the codends at lengths greater than 29 cm for S. norvegicus and 19 cm for S. viviparous. At smaller lengths, size selectivity was undetermined due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Diamond mesh codends are the most widespread and simplest size-selection device used in demersal trawls, and in some fisheries, size selectivity relies solely on the selective properties of this type of codend (Cheng et al 2019). However, diamond mesh codends can pose challenges and yield varying or unsatisfactory results (Robertson and Stewart 1988;Sala et al 2008;Wienbeck 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Diamond mesh codends are the most widespread and simplest size-selection device used in demersal trawls, and in some fisheries, size selectivity relies solely on the selective properties of this type of codend (Cheng et al 2019). However, diamond mesh codends can pose challenges and yield varying or unsatisfactory results (Robertson and Stewart 1988;Sala et al 2008;Wienbeck 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Future research should consider codend diameter differences and their effect on T90 selectivity. These results could be contrasted against studies that used T0 codends, such as Pol et al (2016) and Cheng et al (2019). Additionally, using a T90 codend in a midwater trawl could also reduce the capture of undersized redfish reported by Duplisea (2018).…”
Section: Discussionmentioning
confidence: 96%
“…Bohl (1961) investigated knotless and knotted diamond mesh codends on the East Greenland redfish fishery and found that knotless codends had a smaller selection range than knotted codends. However, Cheng et al (2019) showed no difference in size selectivity of redfish with knotted versus knotless diamond codends in the Icelandic fishery. Hickey et al (1995) compared the selectivity of diamond mesh codends with and without shortened lastridge ropes in the Newfoundland redfish fishery and reported that 90 mm mesh codend with shortened lastridge ropes, which allow the meshes to stay open under strain, performed the best with 1.1% of redfish below 23 cm (versus 13.3% without the shortened ropes) being retained.…”
Section: Introductionmentioning
confidence: 82%
“…To investigate how applying the different design combinations considered would affect the catch pattern in the fishery, we estimated the value of three exploitation pattern indicators, nP − , nP + and nDiscard , for each gear design. These indicators are often used in fishing gear size selectivity studies to supplement assessment solely based on selectivity curves [ 22 , 25 , 38 , 71 73 ]. Specifically, the percentage of individuals retained below ( nP − ) and above ( nP + ) the species-specific minimum conservation reference size (MRCS) was estimated, as well as the discard ratio ( nDiscard ), which quantifies the fraction of hake and blue whiting below MCRS in the total catch (in %).…”
Section: Methodsmentioning
confidence: 99%